Implementation of a STEM and Wasaka Character-Integrated Module to Internalize Wasaka Character - Muhsinah Annisa; Dasim Budimansyah; Mupid Hidayat; Atiek Winarti; Teguh Prasetio (Postgraduate, University of Mataram, 2024)
STEM Education (Science, Technology, Engineering, and Mathematics) plays a crucial role in elementary schools because it provides a strong foundation for students' skill development and understanding in science and technology. STEM education can help students develop critical thinking, problem-solving skills, and creativity from an early age This research aims to implement a STEM-integrated module infused with Wasaka character values to internalize the Wasaka character in students. The Wasaka character, comprising religiousness, resilience, responsibility, and independence, is vital for fostering holistic development. The study utilizes a one-group pre-test-post-test design with pre-test and post-test evaluations to measure the effectiveness of the module in enhancing character development. Data were collected through observations and questionnaires. The results indicate a significant improvement in the internalization of Wasaka character traits following the implementation of the module. The findings suggest that integrating STEM education with local cultural values can effectively contribute to character building. This study highlights the importance of culturally relevant education in shaping students' character.